Contact Pressure between Digital Flexors and Plates for Distal Radius Approaches - Jones, Christopher M.; Melvani, Roshan; Aziz, Keith T.; Abbasi, Pooyan; Means, Kenneth R., Jr. (Journal of Wrist Surgery, 2020)
Background Flexor tendon irritation or rupture following open reduction and volar plate fixation of distal radius fractures can cause significant morbidity and necessitate additional surgical intervention.Objectives To compare the impact of the extended flexor carpi radialis (e-FCR) and standard flexor carpi radialis (FCR) approaches on contact pressures between the flexor tendons and volar distal radius plates.Methods Eight matched pairs of fresh frozen cadavers had each limb randomized to undergo either the e-FCR or standard FCR approach. After the approach, a locking plate was applied to the volar distal radius more distally than ideally to create a worst-case scenario for the digital flexor tendons. Electronic pressure sensors were secured to the volar aspect of each locking plate. Each wrist was pinned in 20 degrees of extension during testing. Using a computer-controlled stepper motor system attached to the digital flexor and extensor tendons, the digits were taken through 4,000 cycles simulating 12 weeks of active flexion and extension.Results There were no statistically or clinically significant differences when comparing the contact pressures of the e-FCR approach with the standard FCR approach at any time intervals. The e-FCR had statistically significantly higher radial-sided contact pressures than ulnar-sided contact pressures during early-to-intermediate testing intervals. These differences resolved at late and final testing intervals.Conclusions When comparing the standard FCR approach with the e-FCR approach, with the wrist in 20 degrees of extension, there is no significant difference in contact pressures that occur between the digital flexor tendons and volar distal radius plates.Clinical Relevance Further study and technique modifications may eventually lead to better methods of avoiding flexor tendon rupture during the volar plating of distal radius fractures.
Keywords: carpal tunnel; distal radius; fracture; tendon rupture; wrist approach